Validity Of Self-Reported Weight, Height And Body Mass Index Among Malaysian Late Adolescents - Kong Pun Pun; Nithiah Thangiah; Hazreen Abdul Majid (Amerta Nutrition, 2021)
Introduction: Malaysia suffers from obesity problems with nearly a quarter of the children and adolescents being overweight or obese. Validated methods are needed to measure the trend of overweight and obesity easily.Objective: The study investigates the precision of Malaysian late adolescents' self-reported height and weight compared to direct-measured methods.Methods:   About 114 young adults aged 19-20 years old participated in this cross sectional study in 2019. Self-reported and direct-measured anthropometrics including height and weight were gathered through phone calls and study instruments. The obtained height and weight values calculates BMI and determines classifications.Results: The ICC value were excellent between reported and measured weight (ICC= 0.94; 95% CI=0.91-0.96), height (ICC= 0.95; 95% CI=0.83-0.98) and BMI (ICC = 0.89; 95% CI=0.78-0.94) were found. Additionally, good agreement observed from B & A plots indicated that the differences between both independent measurement variables were minor and most of the differences were within the area of the limit of agreement at the population level for their anthropometric measurements. The Cohen’s Kappa showed substantial agreement of BMI calculated from reported weight and height (ҡ = 0.61; 95% CI= 0.48-0.74), boys (ҡ = 0.67; 95% CI=0.43-0.91) and girls (ҡ = 0.58; 95% CI=0.43-0.73).Conclusion: This validation study concluded that self-reported height and weight were in agreement with direct-measured methods. This technique can be utilized to assess the anthropometric status of Malaysian late adolescents for population studies.